The Comparison Organizational Theory and Organization Performance on The Process of Enriching Organizational Culture on The Implementation of The Principles Government Organizations In Indonesia - Hartanto, Beni; Rahmat, Basuki (International Journal of Artificial Intelligence Research, 2025)
The purpose of this study is to determine and analyze Comparison Organizational Theory and Organization Performance on The Process of Enriching Organizational Culture on The Implementation of The Principles  Government Organizations In Indonesia.. The research sample consisted of 104 State Civil Apparatus whose duties were related to those studied. The research method used is an explanatory survey approach to explain the relationship between variables through hypothesis testing in the field. Research that uses descriptive surveys and explanatory survey methods is carried out by collecting information from samples directly at the scene of the incident (empirical) through questionnaires with the aim of finding out the opinions of the samples regarding the research problem. And this research uses the Partial Least Squares Structural Equation Modeling analysis technique (PLS-SEM), to model many variables in research  Results and Discussion: To examine the influence of mediator variables, Partial Least Squares Structural Equation Modeling analysis technique (PLS-SEM),to estimate the causal relationship between variables (causal model) that has been determined previously based on the theory. Answering research questions requires correct statistical data processing. This is based on the results of hypothesis testing, the t-statistics results obtained were 3,287 and the significance results (pvalue) obtained were 0.000 (0.000<0.05), so Ho was rejected and Ha was accepted. The test results prove the Comparison Organizational Theory and Organization Performance on The Process of Enriching Organizational Culture This is based on the results of hypothesis testing, the t-statistics results obtained were 2.845 and the significance results (pvalue) obtained were 0.001 (0.001<0.05), so Ho was rejected and Ha was accepted. The test results the the Comparison Organizational Theory and Organization Performance on The Process of Enriching Organizational Culture